Human rights in procedural democracies: a contribution to the debate - José Armando Ponte Dias Júnior; Eneida Desiree Salgado (Revista de Direito Econômico e Socioambiental)
If human rights find an unsafe development in regimes whose public choices are guided by market rules, they also find a fragile development in liberal democracy. Liberal democracy – descriptive, procedural and to some extent minimalist, primarily concerned with formally securing classic individual freedoms – now faces an acute crisis, with its historic achievements threatened by populist and undemocratic ideas. This article, in dialogue with studies on democracy and liberalism, analyzes the relationship between liberal democracy and human rights, in order, in the end, to point out the need for democracy, for its own survival, to expand its horizons towards the promotion of human rights beyond classical freedoms, with the aim of building a materially egalitarian society.